THE EFFECT OF MANAGERIAL OWNERSHIP, PROFITABILITY, SOLVABILITY AND COMPANY SIZES ON PROFIT MANAGEMENT IN PROPERTY AND REAL ESTATE COMPANIES WHICH ARE IN THE INDONESIAN STOCK EXCHANGE PERIOD 2013 – 2017 - Rosa Dwi Agsari (Fakultas Bisnis, 2020)
This study was conducted to examine the effect of Managerial Ownership, Profitability, Solvency and Company Size variables on Profit Management partially on property and real estate companies listed on the Indonesia Stock Exchange in the period 2013-2017. In addition, to examine the feasibility of a regression model of the influence of variable ownership variables Managerial, Profitability, Solvency and Company Size Management simultaneously on property and real estate companies listed on the Indonesia Stock Exchange in the period 2013-2017. This research was conducted on property and real estate companies on the Indonesia Stock Exchange for the period 2013-2017. The determination of the sample in this study uses a non-probability sampling method with a purposive sampling technique in order to obtain a total sample of 8 companies and a total of 40 observations. The data in this study were analyzed using panel data analysis techniques. The results showed that Managerial Ownership, Solvency and Company Size had no effect on Profit Management. Another variable in this study is that profitability has a positive and significant effect on earnings management. Simultaneously Managerial Ownership, Profitability, Solvency and Company Size Towards Profit Management. The predictive ability of the four variables on Profit Management is 22.84% as shown by the amount of Adjusted R-squared of 0.2284 while the remaining 77.16% is influenced by other factors not included in the research model.